Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Aparatur Sipil Negara pada Satuan Polisi Pamong Praja dan Pemadam Kebakaran - Sani, Agus; Muhtar, Entang Adhy; Aripin, Sofjan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Based on initial observations related to the organisational performance of the Pamong Praja Police and Fire Fighting Unit in Malinau Regency is still not optimal, due to a decrease in employee income and limited activity budgets. This study aims to determine the effect of leadership and motivation on employee performance in the agency. This research belongs to the category of explanatory research to explain the causal relationship and test the relationship that occurs between leadership and motivation factors on employee performance. The instrument used is a questionnaire which is then analysed using the OLS (Ordinary Least Squares) method. The research results are as follows (1) leadership has a positive influence on employee performance but the effect is not significant, meaning that when leadership increases performance will also increase, and vice versa. This is because in carrying out their duties and responsibilities they are still faced with limited competencies, facilities, and dynamic and difficult to predict situations in the field (2) motivation has a positive influence on employee performance and the effect is significant, meaning that when motivation increases, performance also increases, and vice versa; This is because carrying out their duties and responsibilities according to the rules (3) leadership and motivation simultaneously have a positive influence on employee performance and the effect is significant. Together, leadership as the ability to influence and direct individuals or groups to achieve pre-determined organisational goals and motivation as the power within a person that influences the direction, intensity and persistence of their own chosen behaviour are able to significantly influence the quality and quantity of something produced by the State Civil Apparatus of the Malinau Regency Pamong Praja Police and Fire Department in carrying out their duties and responsibilities.